The prevalence of visual impairment among children with disability / Noor Shuhada Aziz - Aziz, Noor Shuhada (2016)
Purpose: Visual impairment was reported to be common among children with disability and could significantly impair the independence in quality of life. The objectives of this study were to determine the prevalence of visual impairment and its relationship between demographic data, visual acuity and refractive error among disability children. Method: A total of 27 clinical records of eye examination from year 2012 to 2015 among disability children (12 boys and 15 girls) at community based centre in Selangor aged one to 18 years old were reviewed. Results: The mean age of disability children was 9.85±4.55 years. It showed that 42.31% of the disability children had insignificant refractive error, whereby 34.61% were hyperopia and 23.1% were myopia. The overall prevalence of visual impairment among disability children was 25.93% with boys had higher prevalence of visual impairment (17.81%) than girls (7.41%). There was a strong positive linear relationship between visual acuity and visual impairment (r=0.80, p=0.01), meanwhile age (r=-0.22, p=0.36), gender (r=-0.32, p=0.10), types of disability (r=- 0.37, p=0.07) and refractive error (r=-0.05, p=0.80) were poorly correlated with visual impairment. Conclusion: The outcomes of this study provide a profile on visual impairment status among disability children. The prevalence of visual impairment among children with disability was high. The visual acuity was revealed to be strongest variable that correlated with visual impairment among children with disability. Thus, this profile could help the clinician to be better prepared when dealing with children with any types of disability and also early detection of any visual disorder.